Quality journalism: Is there a future? The evolution of the reference press in the Basque Country and Europe (2001-2014) - Ramírez de la Piscina Martínez, Txema (Universidad del País Vasco, 2016)
The subject of the study is very succinct: the present and future of journalism. The HGH research team, like many experts, both academics and those involved in the profession, is concerned about the consequences of the internal changes which have been affecting the profession. Will these changes have any influence on news quality? Can news quality be evaluated? How? Using which criteria? What is the situation of the Basque language media? And at the highest European level? These research questions are the starting point, the driving force and the end point in this research work. All those taking part in this project were fully aware of the challenges facing them, the seriousness of the situation and also of the unknown factors lying ahead in the future.